The relationships among MAOA, COMT Val158Met, and 5-HTTLPR polymorphisms, newborn stress reactivity, and infant temperament - Bajgarova, Zdenka; Bajgar, Adam (Brain and behavior, 2020)
INTRODUCTION: Variance in hypothalamic-pituitary-adrenal (HPA) axis reactivity is considered to be one of the sources of differences in infant temperament. The cortisol enters into interactions with dopamine and serotonin, so it is expected that polymorphisms in genes coding monoamine metabolism influence both HPA axis reactivity and temperament. METHODS: We therefore explore the relationship among 5-HTTLPR S/L, MAOA H/L, and COMT Val158Met polymorphisms, the stress reaction of newborn infants after a heel stick blood draw (measured by determining salivary cortisol at three time points), and temperament assessed at the age of 3 months using Rothbart's Infant Behavior Questionnaire-Revised (IBQ-R) with a sample of 84 infants. RESULTS: The decrease in the salivary cortisol correlated with nine primary scales and all three secondary scales of IBQ-R. Children with a greater cortisol decrease were assessed as less susceptible to negative emotions, more extraverted, and more regulated. The polymorphisms that were observed were related both to the course of the stress reaction and to temperament. The 5-HTTLPR S allele was connected to higher scores for Negative Emotionality and lower scores for Orienting/Regulatory Capacity. The presence of the MAOA L allele predisposed its carriers to higher scores for Negative Emotionality, lower scores for Orienting/Regulatory Capacity, and a lower decrease in cortisol. The Met allele of COMT Val158Met polymorphism was connected to a higher Positive Affectivity/Surgency and Orienting/Regulatory Capacity and a greater cortisol decrease. CONCLUSIONS: Contrary to previous studies referring mainly basal cortisol and its increase, the results of our study emphasize the importance of cortisol elimination in infant temperament. Another interesting finding was a higher cortisol increase, higher Distress to Limitations, Negative Emotionality, and Approach in MAOA LL homozygotes which are traditionally understood as more vulnerable toward early stress in developing later externalizing behavior.
Keywords: Monoamine Oxidase; Temperament; Female; Infant; Hypothalamo-Hypophyseal System; novorozenec; Catechol O-Methyltransferase; Serotonin Plasma Membrane Transport Proteins; ženské pohlaví; hydrokortison; lidé; Hydrocortisone; Infant, Newborn; chování kojenců; Infant Behavior; monoaminoxidasa; systém hypotalamus-hypofýza; membránové transportní proteiny pro serotonin; temperament; Male; kojenec; polymorfismus genetický; katechol-O-methyltransferasa; mužské pohlaví; Polymorphism, Genetic; Humans